IOT-Based Smart Home Control Design Using Blink Application and Esp8266 Wi-Fi Module - Anggara Trisna Nugraha; Ananda Ismul Azam; Rama Arya Sobhita; Epyk Sunarno (MEIN : Journal of Mechanical, Electrical & Industrial Technology, 2024)
The swift progression of technology has significantly impacted contemporary human existence, leading to an escalating demand for tools that simplify daily tasks. Automation is viewed as a means to reduce time, enhance accessibility, and improve efficiency. Particularly, the adoption of Smart Home technology is becoming increasingly crucial in present times. This research endeavors to develop an innovative prototype for a home equipped with IoT capabilities. The prototype incorporates a range of sensors and components to fulfill various functions: a DHT11 sensor for monitoring room temperature, an MQ-2 sensor for detecting gas leaks, an ultrasonic sensor for object detection, an MC38 magnet sensor for door security, a relay to control lamp switches, and a buzzer for alarms, all managed by a microcontroller. Additionally, the system utilizes a NodeMCU with a Wi-Fi module ESP8266, facilitating communication and control through the Blynk App. The Research and Development (R&D) methodology was employed to create this IoT-enabled Smart Home prototype, aiming to enhance user convenience in daily living.